Meteoric diagenesis and dedolomite fabrics in precursor primary dolomicrite in a mixed carbonate–evaporite system - Hauck, Tyler E.; Corlett, Hilary; Grobe, Matthias; Walton, Erin L.; Sansjofre, Pierre (My University, 2018)
Dedolomitization is a common diagenetic process in shallow burial environments and is often associated with sulphates in mixed carbonate-evaporite successions. In these settings, elevated Ca (super 2+) /Mg (super 2+) ratios necessary for dedolomitization result from the dissolution of sulphate phases by the incursion of undersaturated groundwater. Reported dedolomite textures from other studies are varied, but the most prevalent is a rhombic texture interpreted to result from the partial to complete pseudomorphic replacement of secondary dolomite rhombs formed in the burial diagenetic realm. In this study of primary cryptocrystalline to finely crystalline dolomicrites in the Prairie Evaporite Formation of north-eastern Alberta, dedolomitization has resulted in sutured to loosely packed mosaics of dedolomite that range from subhedral to distinctly euhedral (rhombic) crystal fabrics; however, no prior aggrading neomorphism producing dolomite rhombs is evident in the precursor dolomicrites. Non-pseudomorphic dedolomitization of the dolomicrites results in textures that include rhombic dedolomite crystals with cloudy cores comprising remnant dolomicrite and clear rims. These textures are similar to those observed in the pseudomorphic dedolomitization of secondary dolomite rhombs. The Prairie Evaporite Formation of north-eastern Alberta has experienced extensive karstification near the erosional margin of the sedimentary succession. Dedolomitization of dolomicrites occurs in marker beds within the Prairie Evaporite succession associated with evaporite karstification. Along with stratigraphic and petrographic considerations, stable isotope results support the interpretation of a shallow dedolomitization event influenced by meteoric waters derived from the basin margin. Negative delta (super 18) O and low delta (super 13) C values (averages of -13.6 ppm (sub VPDB) and 0.5 ppm (sub VPDB) , respectively) of the dedolomite, compared with those of the primary dolomicrite (averages of -6.0 ppm (sub VPDB) and 1.2 ppm (sub VPDB) , respectively), point to isotopically light diagenetic fluids. These results show that rhombic dedolomite textures can form through shallow, non-pseudomorphic dedolomitization of dolomicrites by meteoric fluids in the presence of sulphates, with resulting textures that are similar to the pseudomorphic dedolomitization of secondary dolomite rhombs.
Keywords: stable isotopes; rhombs; Prairie Evaporite Formation; porosity; meteoric diagenesis; evaporite karst; dedolomite